Effective mass of band edges in a (20)InAs-(6)Al0.1Ga0.9Sb superlattice - Geri Kibe AK. Gopir (Universiti Kebangsaan Malaysia, 1999)
The curvature method and the f-sum rule are used to calculate the effective mass of electrons and holes at the Brillouin zone band edges of a (20)InAs(6)Al0.1Ga0.9Sb superlattice. The electronic and optical parameters used in the calculations for this type II semiconductor superlattice are derived from the relativistic empirical pseudopotential method. In this superlattice system the calculated effective masses for the carriers are anisotropic and differ from those of the various reported semiconductor heterostructures. These results indicate that the carrier effective masses are dependent on certain factors such as polarisation, constituent layer composition and layer length. The calculated effective masses of electrons in this III- V semiconductor heterostructure are found to be larger than those in Hg1-xCdxTe alloys with similar band gaps corresponding to cutoff wavelengths near 10 μm. This makes the InAs-AlGaSb superlattice system a potential competitor to the present standard material of HgCdTe for far infrared applications.